Brønsted acid-promoted C–F bond activation in [P, S]-ligated neutral and anionic perfluoronickelacyclopentanes. Issue 45 (24th September 2015) - Giffin, Kaitie A.; Korobkov, Ilia; Baker, R. Tom
Abstract : Bidentate phosphinothiol ligand induces C–F bond functionalization in perfluoronickelacycles. Abstract : Treatment of L2 Ni(CF2 )4 4a–c (L = PPh3, PPh2 Me, pyridine) with an external Lewis acid (trimethylsilyl triflate) gives new L-functionalized fluoronickelacyclopentanes5a–c . Complexes L2 Ni(CF2 )4 4a, b react with the thiol form of the bidentate ligand 1, 2, 4-(HS)(Ph2 P)Me(C6 H3 )[P, SH] through a unique Brønsted acid-promoted Cα –F bond activation mechanism, affording phosphine-functionalized nickelacycles bearing a phosphinothiolate ligand6a–b . Furthermore, substituting monodentate ligands in L2 Ni(CF2 )4 4a–c with the deprotonated form of the bidentate ligand[P, S − ] leads to the first anionic perfluoronickelacycle7 . The anionic metallacyle reacts with phosphonium salts [PHPh3 ](Br) and [PHPh2 Me](Br) to yield HF and phosphine-functionalized nickelacycles6a, b that still contain the terminal thiolate moiety.